Grotesque visions - Haakenson, Thomas O., 1972- (New directions in German studies, 2021)
"Grotesque Visions focuses on the radical avant-garde interventions of Salomo Friedländer (aka Mynona), Til Brugman, and Hannah Höch as they challenged the questionable practices and evidentiary claims of late-19th- and early-20th-century science. Demonstrating the often excessive measures that pathologists, anthropologists, sexologists, and medical professionals went to present their research in a seemingly unambiguous way, this volume shows how Friedländer/Mynona, Brugman, Höch, and other Berlin-based artists used the artistic grotesque to criticize, satirize, and subvert a variety of forms of supposed scientific objectivity. The volume concludes by examining the exhibition Grotesk!: 130 Jahre Kunst der Frechheit/Comic Grotesque: Wit and Mockery in German Arts, 1870-1940. In contrast to the ahistorical and amorphous concept informing the exhibition, Thomas O. Haakenson reveals a unique deployment of the artistic grotesque that targeted specific established and emerging scientific discourses at the turn of the last fin-de-siècle"--